Role of refractive-index surfaces on helicon-wave propagation - Singh R.N.; Pandey N.L. (My University, 2025)
The dispersion equation accounting for the finite phenomenological collision frequency and the electron-hole effective mass ratio in a semiconductor plasma has been derived. The refractive-index surfaces for the dimensionless collision parameter Z and the effective mass ratio d have been computed. It is shown that the refractive-index surfaces are very sensitive to changes in the collision frequency and are comparatively less sensitive to changes in effective mass ratio. The effect of the refractive-index surface on low-frequency helicon-wave propagation in a n-type InSb semiconductor plasma has been discussed. It is argued that the deformations and changes in refractive-index surfaces would be of significant diagnostic value. © 1975 The American Physical Society.